Teacher Elicitation and Student Reply in EFL Classroom Discourse: Evidence from An Islamic Junior High School - Aji Gapiano; Fakry Hamdani; Muhammad Aminuddin (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
Classroom interaction plays a central role in English as a Foreign Language (EFL) learning by providing opportunities for learners to participate in communicative exchanges and develop language competence. Despite extensive research on classroom discourse, limited attention has been given to the interactional relationship between elicitation and reply acts, particularly in Islamic educational contexts. This study examines how elicitation and reply acts are realized and interact in classroom discourse and identifies the dominant interactional patterns in an EFL classroom. Drawing on Sinclair and Coulthard’s (1975) discourse framework, the study employed a qualitative classroom discourse analysis with descriptive quantitative support. Data were collected through classroom observations and audio recordings of four English lessons involving a seventh-grade class at an Islamic junior high school in Indonesia. The interactions were transcribed, coded, and analyzed using the Rank Scale model. The findings revealed that elicitation (20.27%) and reply (18.54%) were the two most frequent discourse acts, indicating that classroom interaction was predominantly organized through teacher-initiated question-and-answer exchanges within the Initiation–Response–Feedback (IRF) sequence. The analysis further showed that elicitation and reply functioned as interconnected interactional mechanisms, while re-initiation, checking, listing, and repetition supported participation and discourse continuity. The study contributes to classroom discourse research by providing an act-level understanding of teacher–student interaction in an Islamic EFL classroom.